An Analysis of Factors Affecting Flowslide Deposit Morphology Using Taguchi Method - Zhao Duan; Yan-Bin Wu; Hao Tang; Jian-Quan Ma; Xing-Hua Zhu (Advances in Civil Engineering)
Flowslides, as one type of landslides, are becoming a research hotspot due to their high speed and long runout distance, which can cause tremendous damage and economic loss. The scale of damage and deposit morphology of flowslide is closely related to factors like deposit volume, slope height, and slope angle. In order to assess the influence of these factors, a sandbox apparatus is developed, and the Taguchi method is used to design an experimental scheme to analyze the results of factors affecting the deposit morphology of flowslide. The results show that the factor that has the greatest impact on flowslide deposit morphology is slope angle, followed by the influence of volume and slope height. As slope angle increases, the maximum width, maximum length, area, and length-width ratio of the deposit first increase and then decrease. In addition, there should be a critical angle in the changes of deposit morphology that is between 60° and 70° under the experimental conditions. When the volume is 5.4 × 10−3 m3, the slope angle is 70°, the slope height is 0.90 m, and the changes of deposit morphology of the flowslide are the largest. In this study, considering the slope angle as a single variable, there is a single upheaval for a slope angle of 40° and 50° and a double upheaval at 60° and 70°. The formation mechanism of the upheaval is analyzed based on the Mohr-Coulomb criterion and considered properties of the material. The apparent friction coefficient of a flowslide is spatially and lithologically different and increases nonlinearly as the slope angle increases. The initial benchmark of the slope angle and apparent friction coefficient curve are affected by the friction coefficient of the material; the position of the inflection point at which the curve increases rapidly is affected by the coefficient of velocity restitution.